NUTRITION LABELLING ON PREPACKED FOODS: OPINION AND SUGGESTIONS OF PORTUGUESE FOOD AND NUTRITION PROFESSIONALS - Vareiro,Daniela (2021)
ABSTRACT INTRODUCTION: Labelling is an important tool for food and nutrition professionals since it provides information on food safety and nutrition. OBJECTIVES: The aim was to analyse the differences in food and nutrition professionals’ opinions regarding nutrition labelling on prepacked foods. METHODOLOGY: A cross-sectional study was conducted, using a non-probabilistic sample of professionals, by contacting several Portuguese entities in food and nutrition. The eligibility criteria included being 18 years old and over, living and working in Portugal, and having a professional activity in this area. An online self-administered survey was developed, including questions about labelling (importance, reading, use, trust, satisfaction, and influence in food choices). The main changes in the European Union labelling rules about the content, presentation and legibility of the mandatory information were analysed. The present paper focuses on the answers to the open-ended question on suggestions to improve nutrition labelling. RESULTS: From the 297 participants, 33 (11.1%) provided answers to the open-ended question, which were subsequently grouped into six categories. These professionals demonstrated the least satisfaction with the label information namely the specific technical terms, the quantity of information, the symbols used and the nutritional claims. They showed the least agreement with the presentation and content of the nutrition information, implemented by Regulation (EU) No 1169/2011. Two improvements were proposed: the simplification of the labelling information and the understanding of its usefulness as it is currently presented, to provide perceptible and useful information to the consumer. CONCLUSIONS: Nutrition labelling educational tools should be developed, in order to promote nutrition literacy and lead to consumer’s empowerment.